Strategi Guru IPS dalam Menanggulangi Kenakalan Remaja Melalui Pendidikan Karakter - Anggela, Feby; Irwan, Irwan; Nurniswah, Nurniswah (IJOCE: Indonesia Journal of Civic Education, 2026)
This study aims to describe the strategies of social studies teachers in tackling juvenile delinquency through character education at SMP Negeri 6, Bengkulu City. The research method used was qualitative with a descriptive approach. Data were collected through interviews, observation, and documentation. The results showed that the strategies used by social studies teachers were divided into two approaches: preventive and curative. Preventive strategies were carried out through the integration of character values ​​in learning, role models, providing motivation, and collaboration with parents. Meanwhile, curative strategies were implemented in the form of reprimands, coaching, counseling, and collaboration with guidance and counseling teachers. In conclusion, this study confirms that character education through social studies learning can be an important instrument in reducing juvenile delinquency.   Keywords: Social Studies Teacher Strategies, Character Education, Juvenile delinquency